The Need of Monitoring Forest Fires through Burned Area Mapping in Indonesia - Risty Khoirunisa (USN Kolaka, 2021)
Forest fires have become a regular phenomenon in Indonesia, especially in the dry season. They can be caused by natural and anthropogenic factor. Since Indonesia’s soil, especially Sumatra and Kalimantan, is a peatland type, this type of soil is highly inflammable, thus a small fire can easily spread and become massive. This phenomenon provenly disturbs the balance of the ecosystem and socio-economy of the affected country. Previous forest fires resulted in a higher risk of respiratory problems and increased mortality or the death of infants and children. The loss of biodiversity and the increasing amount of Green House Gas (GHG) Emissions that affected the change of climate is also the effect caused by those. For those reasons, the need of monitoring forest fires is essential, especially in climate change mitigation as fire disturbance is one of the key variables in it. This paper will further discuss the method of monitoring through burned area mapping using remote sensing techniques.